Black carbon and organic carbon dataset over the Third Pole - Kang, Shichang; Zhang, Yulan; Chen, Pengfei; Guo, Junming; Zhang, Qianggong; Cong, Zhiyuan; Kaspari, Susan; Tripathee, Lekhendra; Gao, Tanguang; Niu, Hewen; Zhong, Xinyue; Chen, Xintong; et al. (Earth System Science Data, 2022)
Abstract. The Tibetan Plateau and its surroundings, also known as the Third Pole, play an important role in the global and regional climate and hydrological cycle. Carbonaceous aerosols (CAs), including black carbon (BC) and organic carbon (OC), can directly or indirectly absorb and scatter solar radiation and change the energy balance on the Earth. CAs, along with the other atmospheric pollutants (e.g., mercury), can be frequently transported over long distances into the inland Tibetan Plateau. During the last decades, a coordinated monitoring network and research program named “Atmospheric Pollution and Cryospheric Changes” (APCC) has been gradually set up and continuously operated within the Third Pole regions to investigate the linkage between atmospheric pollutants and cryospheric changes. This paper presents a systematic dataset of BC, OC, water-soluble organic carbon (WSOC), and water-insoluble organic carbon (WIOC) from aerosols (20 stations), glaciers (17 glaciers, including samples from surface snow and ice, snow pits, and 2 ice cores), snow cover (2 stations continuously observed and 138 locations surveyed once), precipitation (6 stations), and lake sediment cores (7 lakes) collected across the Third Pole, based on the APCC program. These data were created based on online (in situ) and laboratory measurements. High-resolution (daily scale) atmospheric-equivalent BC concentrations were obtained by using an Aethalometer (AE-33) in the Mt. Everest (Qomolangma) region, which can provide new insight into the mechanism of BC transportation over the Himalayas. Spatial distributions of BC, OC, WSOC, and WIOC from aerosols, glaciers, snow cover, and precipitation indicated different features among the different regions of the Third Pole, which were mostly influenced by emission sources, transport pathways, and deposition processes. Historical records of BC from ice cores and lake sediment cores revealed the strength of the impacts of human activity since the Industrial Revolution. BC isotopes from glaciers and aerosols identified the relative contributions of biomass and fossil fuel combustion to BC deposition on the Third Pole. Mass absorption cross sections of BC and WSOC from aerosol, glaciers, snow cover, and precipitation samples were also provided. This updated dataset is released to the scientific communities focusing on atmospheric science, cryospheric science, hydrology, climatology, and environmental science. The related datasets are presented in the form of excel files. BC and OC datasets over the Third Pole are available to download from the National Cryosphere Desert Data Center (https://doi.org/10.12072/ncdc.NIEER.db0114.2021; Kang and Zhang, 2021).

Fossil Fuel Combustion Emission From South Asia Influences Precipitation Dissolved Organic Carbon Reaching the Remote Tibetan Plateau: Isotopic and Molecular Evidence - Li, Chaoliu; Chen, Pengfei; Kang, Shichang; Yan, Fangping; Tripathee, Lekhendra; Wu, Guangjian; Qu, Bin; Sillanpää, Mika; Yang, Di; Dittmar, Thorsten; Stubbins, Aron; Raymond, Peter A. (Journal of Geophysical Research: Atmospheres, 2018)
The dissolved organic carbon in precipitation (water‐soluble organic carbon, WSOC) can provide a carbon subsidy to receiving ecosystems. The concentrations, isotopic signatures (δ13C/Δ14C), and molecular signatures (transform ion cyclotron mass spectrometry) of WSOC being delivered to Nam Co—a remote site on the inland Tibetan Plateau (TP)—were compared to those of WSOC in the snowpack, and in wet deposition from urban cities fringing the TP. The average WSOC concentration at Nam Co (1.0 ± 0.9 mg C L−1) was lower than for the large cities (1.6 to 2.3 mg C L−1) but higher than in the snowpack samples (0.26 ± 0.09 mg C L−1). Based upon radiocarbon data, it is estimated that 15 ± 6% of Nam Co WSOC was fossil derived, increasing to 20 ± 8% for snowpack WSOC, 29 ± 4% for Lhasa WSOC, and 34 ± 8% for the three cities. Transform ion cyclotron mass spectrometry results revealed that the abundance of dissolved black carbon and sulfur‐containing molecules of WSOC increased in the order Nam Co < snow pack < urban. The enrichment in 14C and depletion in dissolved black carbon and sulfurous organic molecules of Nam Co WSOC was suggestive of low, but still detectable inputs of fossil‐derived organics to WSOC on the remote TP. Backward air mass trajectories for the precipitation events at Nam Co suggested that the fossil fuel contributions to WSOC in Nam Co region originated mainly from South Asia. This study provides novel radiocarbon age, chemistry, and source evidence that anthropogenic WSOC is delivered to the remote TP, one of the most remote regions on Earth.

Aged dissolved organic carbon exported from rivers of the Tibetan Plateau - Qu, Bin; Sillanpää, Mika; Li, Chaoliu; Kang, Shichang; Stubbins, Aron; Yan, Fangping; Aho, Kelly Sue; Zhou, Feng; Raymond, Peter A. (PLOS ONE, 2017)
The role played by river networks in regional and global carbon cycle is receiving increasing attention. Despite the potential of radiocarbon measurements (14C) to elucidate sources and cycling of different riverine carbon pools, there remain large regions such as the climate-sensitive Tibetan Plateau for which no data are available. Here we provide new 14C data on dissolved organic carbon (DOC) from three large Asian rivers (the Yellow, Yangtze and Yarlung Tsangpo Rivers) running on the Tibetan Plateau and present the carbon transportation pattern in rivers of the plateau versus other river system in the world. Despite higher discharge rates during the high flow season, the DOC yield of Tibetan Plateau rivers (0.41 gC m-2 yr-1) was lower than most other rivers due to lower concentrations. Radiocarbon ages of the DOC were older/more depleted (511±294 years before present, yr BP) in the Tibetan rivers than those in Arctic and tropical rivers. A positive correlation between radiocarbon age and permafrost watershed coverage was observed, indicating that 14C-deplted/old carbon is exported from permafrost regions of the Tibetan Plateau during periods of high flow. This is in sharp contrast to permafrost regions of the Arctic which export 14C-enriched carbon during high discharge periods.
Keywords: Carbon cycle; Carbon dioxide; Climate change; Rain; Rivers; Surface water; Tibetan people; TIBETAN PLATEAU